Recent Advances In 3d Bioprinting: A Review Of Cellulose-based Biomaterials Ink - Wan Nazihah Liyana Wan Jusoh; Mohd Shaiful Sajab; Peer Mohamed Abdul; Hatika Kaco (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA